Lesbianisme Santri Di Pondok Pesantren - Hj. Siti Nur Asiyah (LPPM IAIN Sorong, 2015)
Lesbi is one of the small parts of social community. Many of ordinary eople do not want to know and understand them. People perception shows that it is social human life. In fact, the lesbians want to exist and express into group social community and make it as a place for accommodating their needs. Nowadays, with facebook, they can communicate fast and easily to their friends in sharing information also to introduce and look for a partner. They realize that as human being they have same need to be fulfilles and can be accepted into social community. Political and legal realities in Indonesia are seen differently by each individual. There is a view that politics and law (the wheels of government) has been running well. There is also a view that politics and law are still very less in implementation. This situation makes the emergence of many forms of resistance (opposition expression) that is delivered by the community. This resistance statement is conveyed through the hard form or known by the demonstration that will bring unrest, or in a subtle form, namely in the arts. The song is born as a form of articulation that society has not been exposed to the public. What the public has perceived only in community conversation without the realization to submit to the competent authorities such as government and the police. In Madrasah of Gontor there is problem about this discourse. So, this article describes it